Left ventricular remodelling patterns after MitraClip implantation in patients with severe mitral valve regurgitation: mechanistic insights and prognostic implications. (11th July 2018) - Brouwer, Hiske J; Den Heijer, Marc C; Paelinck, Bernard P; Debonnaire, Philippe; Vanderheyden, Marc; Van De Heyning, Caroline M; De Bock, Dina; Coussement, Patrick; Saad, Georges; Ferdinande, Bert; Pouleur, Anne-Catherine; Claeys, Marc J
Abstract: Aims: The effect of MitraClip implantation on left ventricular (LV) remodelling has been shown to be highly variable. The present study wants to assess patterns of LV remodelling and its relationship with outcome. Methods and results: Serial echocardiography before, 1 and 6 months after MitraClip implantation was performed in 79 pts with severe mitral regurgitation (MR) (age 74 ± 10 years, New York Heart Association III/IV 80%, LV ejection fraction 38 ± 13%, logistic EuroSCORE 21 ± 15, and functional MR 81%). LV reverse/adverse remodelling was defined as a >15% decrease/>10% increase in LV end-diastolic volume (LVEDV), respectively. Patients were followed over a period of 32 ± 16 months with all-cause mortality as the primary endpoint. A sustained (6 month) reduction of MR ≤ 2 post-MitraClip implantation was observed in 83% of patients. The average decrease in LVEDV 6 months after intervention was 13% ± 16%. Reverse remodelling at 6 months occurred in 40 patients (51%), and adverse remodelling occurred in 6 patients (8%). Patients with adverse remodelling showed a 38% increase of LVEDV at 1 month vs. no early change in LVEDV in patients with reverse remodelling. During follow-up, a total of 25 patients (32%) died. Patients with adverse remodelling died more frequently than patients with reverse remodelling [67% vs. 27%, adjusted odds ratio of 5.6 (95% CI 1.5–21)]. Conclusion: The majority of patients undergoing MitraClip implantation for severe MR showed LV reverse remodelling. However, there was a small group in whom afterload mismatch resulted in sustained adverse remodelling with subsequent high mortality.